Liquid-structure interaction coupled motion of a cantilever plate inside a container: An experimental investigation - Maiti P.R.; Bhattacharyya S.K. (My University, 2025)
The liquid-structure interaction response of a cantilever plate that may be treated as baffle, placed inside a partially liquid filled prismatic container, is carried out experimentally on a shake table that performs sinusoidal motion in horizontal plane. The slosh-induced forced vibration response of the cantilever plate is carried out for different sizes of plate placed at different positions below the free surface of the container. The displacement and velocity response of the rigid and flexible plate is measured and presented for different external base excitation. The motion of liquid around the tip of the plate is visualized by dispersion of dye around the plate during vibration of liquid-container-plate system. A vortex is formed at the sharp edges of the cantilever plate when the plate vibrates in liquid of the container and is gradually dispersed in the liquid medium. The mechanism of vortex formation at the cantilever plate and its shedding in liquid medium is discussed. © 2020 by Begell House, Inc. www.begellhouse.com